Three new species of Bryopharsos Quate, 1996 (Diptera, Psychodidae, Psychodinae) from the Neotropical Region - Bravo, Freddy; Araújo, Maíra Xavier (Zootaxa, 2019)
Bryopharsos Quate, 1996 is a Neotropical genus with four species, all from Central America. This paper describes three new species from Brazil, Bryopharsos uncinatum sp. nov., Bryopharsos paulistensis sp. nov. and Bryopharsos amazonensis sp. nov. A wider concept to the genus Bryopharsos is proposed here to include the species from Brazil. We also provide an identification key for males of the genus.